SZ_GERICHTE STK 2024 21 vom 8. April 2025 , Vergewaltigung, Drohung, versuchte Nötigung, Landesverweis - SZ Gerichte (2025)
Vergewaltigung, Drohung, versuchte Nötigung, Landesverweis | Strafgesetzbuch